Gêneros encarcerados: uma análise trans.viada da política de alas LGBT no Sistema Prisional de Minas Gerais - Gabriela Almeida Moreira Lamounier (2018)
In Brazil, criminal practices are historically associated with the control of the black population. Therefore, the racist paradigm that underpins the methodology determines the working dynamics of prisons: the denial of the humanity of people who are incarcerated. When denouncing various abuses to which people that are living in the LGBT Wards are subjected to, a queer prisoner shared with me that we are prisoners. We are not dead, or trash, or animals. The main research goal was to analyse the Reabilitation, Social Reintegration and Professionalization Program (LGBT Wards) of the Minas Gerais (MG) Prison System, from the perspective of the prisoners. Thus, I considered that incarcerated people produce knowledge about the prison system. To this end, I realized visits, conversations and exchanged affection with the people who were incarcerated in the Annex, name for the LGBT Ward in the prison of Vespasiano; I examined legislation and state action plans on criminal policies and LGBT rights; I conducted a semi-structured interview with the current coordinator of the Special Office for Sexual Diversity Policies of Minas Gerais (CODS) about the work done regarding the reality of vulnerability of bichas and travestis imprisoned in MG; and I analised journalistic pieces regarding the LGBT Wards policies in MG and in Brazil. By considering the powerful approchement between social psychology and ethnography, I choose to complement the analyzes and descriptions with expressions of affection, slangs, personal reflections and clippings from the field book elaborated for the visits in the Annex. The main questions that guided this research were: how do the people who are there, imprisoned, week after week, day after day, hour after hour, analyze that space? What criticisms do they make? What changes they demand? What do the people in prison create, reflect, and produce on the subject of gender incarceration? How to build a text that helps complexifying the debate on gender and sexuality in the prison system? Complaints, jokes, affection, laughter, tears. Impotence, fear, urgency. From the relationship I build with people incarcerated in Vespasianos Annex and from the contact with feminist references, critical criminology and queer abolitionist anarchism, it was inevitable to conclude that the criminal policies, even those paradoxically implemented in a democratic vocabulary of security for the LGBT population, work to qualify the basis for a unrighteous policy of livelihoods: the politics of punishment and mass imprisonment. Thus, although urgent and necessary in the short term, a LGBT Ward policy may collaborate to strengthen criminal policies that act from an order that is contrary to the very existence of queer and deviant people.